Patterns of Migration in Central Europe
XIX, 301 p.
Keywords: Patterns of Migration in Central Europe brings together new material on migration in the region: Poland, Hungary, the Czech Republic and Slovakia. In the last ten years, these countries have changed from being countries of emigration to countries of immigration. As the next candidates for membership to the European Union, migration has become a particularly important topic for these countries. This book is designed as a key text for those interested in the development of the region and in European migration more generally.